DIRECTIONS FOR IMPROVING THE ECONOMIC EFFICIENCY OF INDUSTRIAL ENTERPRISES OF HOUSING CONSTRUCTION IN UZBEKISTAN - Nozima Nigmatjonova Ulamasjanovna (Scholar Express Journals, 2023)
This article explores strategies to enhance the economic efficiency of industrial enterprises engaged in housing construction within Uzbekistan. The housing sector plays a crucial role in the country's economic development, and optimizing the operations of industrial enterprises can lead to significant improvements in cost-effectiveness, resource utilization, and overall productivity. This article proposes a multi-faceted approach encompassing various methods, case studies, and recommendations to achieve these goals.
Keywords: Economic efficiency; industrial enterprises; housing construction; Uzbekistan